Implementing CSR in the fashion industry: measuring the designers´ perceptions and commitment - Plonka, Magdalena Barbara (2019)
This dissertation contributes to the existing knowledge on the implementation of Corporate Social Responsibility in the apparel industry. This is achieved through an in-depth analysis of the designers’ perceptions and roles in CSR with regard to organisational issues, as well as the exploration of their commitment on the one hand and the overall adaptation of CSR in the contemporary clothing industry on the other. As the garment industry is facing many challenges connected with ethical and ecological matters, the chief objective of this study has been to find the best tools for CSR implementation in the fashion industry as seen through the design’s and the designers’ lenses. With the help of a comprehensive literature review on the one hand and a mixed methodological approach on the other—namely measuring the designers’ perceptions through surveys and interviews—this research investigates the apparel environment in order to provide a suitable definition of Corporate Social Responsibility and the processes of its implementation. As it turns out, the designers influence the CSR practice significantly as they play a key role in CSR implementation in the clothing industry. From these creators’ perspective, their contribution to ethical corporate policies is most visible through a number of elements, i.e. choices regarding sustainable technologies, educational and communicational commitment to their work environment, their influence on the executives’ decisions, and their role in collecting data on the green consumers’ preferences. 16 However, these designers’ CSR functions seem to be neglected or marginalised. The research points to factors such as: a dialogue gap between the creators, the executives and other team members; the role of other positions as exemplified through the middle management blocking the designers’ input into CSR; and the lack of the creators’ decisional power within the organisation. By measuring the fashion designers’ perceptions, the study concludes that their general role in CSR performance is meaningful, but underestimated and hindered through the system. As a result, the commitment section includes directions on new responsibilities for designers in the business system. These duties comprehend new roles in communication, in selecting technologies, in conducting outsourcing and in developing better strategies for expanding consumers' awareness and compromise to CSR's practices. In addition, designers' commitment to CSR aims to develop creative and unique design concepts, to expand the compromise with local stakeholders and to develop new approaches in the slow fashion design. Furthermore, to expand the knowledge basis this topic addresses several measures in the academic and education fields. Additionally, the dissertation suggests the creation of a platform for stakeholders’ further discussions on the expansion of the concept. Within this framework, the ethical guidelines included in self-regulations would help to develop tightened cooperation between the designers and the executives. This way, the designers’ decisional and communicational position with regard to CSR would get unlocked. The discoveries behind this thesis are novel and consist of findings that should prove useful both for the CSR theory development and the practical adaptation of CSR in the fashion industry.